2013
DOI: 10.1177/0333102413502736
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression profiling in brains of familial hemiplegic migraine type 1 knock-in mice

Abstract: Background: Various CACNA1A missense mutations cause familial hemiplegic migraine type 1 (FHM1), a rare monogenic subtype of migraine with aura. FHM1 mutation R192Q is associated with pure hemiplegic migraine, whereas the S218L mutation causes hemiplegic migraine, cerebellar ataxia, seizures, and mild head trauma-induced brain edema. Transgenic knock-in (KI) migraine mouse models were generated that carried either the FHM1 R192Q or the S218L mutation and were shown to exhibit increased Ca V 2.1 channel activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This is in line with our previous study that identified only minor differences in cortical gene expression between FHM1 mice and WT under naïve conditions [20]. Also, the CSD effect was relatively small, which shows that the brain is relatively resistant with respect to changing the expression of genes even after a major perturbation such as multiple CSD events.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in line with our previous study that identified only minor differences in cortical gene expression between FHM1 mice and WT under naïve conditions [20]. Also, the CSD effect was relatively small, which shows that the brain is relatively resistant with respect to changing the expression of genes even after a major perturbation such as multiple CSD events.…”
Section: Discussionsupporting
confidence: 91%
“…In that respect, it is noteworthy that naïve trigeminal ganglia of FHM1 R192Q migraine mice exhibit a pro-inflammatory phenotype with a higher number of activated macrophages, activated microglia and increased cytokine expression levels [42–45]. In the caudal cortex, in which CSD events originate, only nine genes are differently expressed in naïve FHM1 mutant mice [20]. Of those genes, Camkk1, Gpr34, Tom1l2 and Cort are linked to inflammation, thus providing some evidence that a pro-inflammatory state may also exist in the naïve FHM1 R192Q cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For migraine, no gene expression data from disease-conditions are available. Few gene expression profiling studies have been carried out for migraine, i.e., in whole blood of episodic and chronic migraine patients (Hershey et al 2004 ) and menstrual migraine patients (Hershey et al 2012 ), in immortalised cell lines of migraine with aura patients (Nagata et al 2009 ), and in brain material of transgenic KI FHM1 mice (de Vries et al 2014 ), but no overlapping deregulated genes or pathways have been identified. Nor is there a large set of causal genes, except for three genes ( CACNA1A, ATP1A2 and SCN1A ) (De Fusco et al 2003 ; Dichgans et al 2005 ; Ophoff et al 1996 ) that have been identified for FHM, that can guide gene identification efforts in the common forms of migraine.…”
Section: Introductionmentioning
confidence: 99%
“…However, while this particular PLC can affect lipid signaling it would not trigger IP 3 release. More to the point of this thesis, an RNA expression dataset from R192Q and S218L knock-in mice tentatively identified PLCβ as an upregulated gene in the cerebellum from S218L preparations(DE VRIES et al 2014). Subsequent studies have not followed up on this lead.…”
mentioning
confidence: 97%